2016
DOI: 10.1155/2016/3459246
|View full text |Cite
|
Sign up to set email alerts
|

Unique Aspects of Cryptochrome in Chronobiology and Metabolism, Pancreaticβ-Cell Dysfunction, and Regeneration: Research into Cysteine414-Alanine Mutant CRY1

Abstract: Cryptochrome proteins (CRYs), which can bind noncovalently to cofactor (chromophore) flavin adenine dinucleotide (FAD), occur widely among organisms. CRYs play indispensable roles in the generation of circadian rhythm in mammals. Transgenic mice (Tg mice), ubiquitously expressing mouse CRY1 having a mutation in which cysteine414 (the zinc-binding site of CRY1) being replaced with alanine, display unique phenotypes in their circadian rhythms. Moreover, male Tg mice exhibit symptoms of diabetes characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Animal models revealed that when mice were subjected to daily restraint stress and cage-switch stress for 1 week, they displayed significant activation of the immune system and development of hypertension (Marvar & Harrison, 2012) by mechanisms explained in Figure 3. Findings from a large pan-European epidemiological study in 124,808 diabetes-free subjects indicate that job strain is a risk factor for type 2 diabetes in men and women independent of other lifestyle factors such as obesity and physical inactivity (Nyberg et al, 2014). A meta-analysis of nine casecontrol and cohort studies of good methodological quality showed positive associations between hypertension and job strain (Babu et al, 2014).…”
Section: Mental Stress Effects On Oxidative Stress and Cardiovasculmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models revealed that when mice were subjected to daily restraint stress and cage-switch stress for 1 week, they displayed significant activation of the immune system and development of hypertension (Marvar & Harrison, 2012) by mechanisms explained in Figure 3. Findings from a large pan-European epidemiological study in 124,808 diabetes-free subjects indicate that job strain is a risk factor for type 2 diabetes in men and women independent of other lifestyle factors such as obesity and physical inactivity (Nyberg et al, 2014). A meta-analysis of nine casecontrol and cohort studies of good methodological quality showed positive associations between hypertension and job strain (Babu et al, 2014).…”
Section: Mental Stress Effects On Oxidative Stress and Cardiovasculmentioning
confidence: 99%
“…Thereby, these findings provide a feasible mechanism how oxidative stress may cause a dysregulation of the circadian clock and accordingly cause large (adverse) changes in clock‐regulated genes in response to environmental and classical risk factors. Interestingly, mice overexpressing a zinc binding deficient mCRY1(C414A) mutant protein showed a long 28‐hr circadian period, abnormal entrainment behaviour as well as symptoms of diabetes, including reduced cell proliferation and insulin secretion (hypoinsulinaemia; Okano, 2016), clearly demonstrating the functional importance of zinc‐dependent mCRY1/mPER2 complex formation for circadian dynamics and metabolic regulation. Overall, the structural analyses of mouse cryptochromes suggest an important role of cysteine redox modifications and of a zinc‐sulphur complex for the general regulation of the circadian clock‐dependent gene expression by the temporal redox oscillations observed in most tissues and in particular the redox regulation of hypo‐ and hyperinsulinaemia with development of diabetes.…”
Section: Oxidative Stress Redox Regulation and Circadian Clockmentioning
confidence: 99%
“…Cryptochrome proteins (CRYs) play indispensable roles as key constituents in the molecular time keeping processes underlying the mammalian circadian clock [13]. We previously generated transgenic mice (previously labeled as CRY1-AP Tg mice [46] or afterward C414A CRY1 Tg mice [3]: hereinafter designated as Tg mice) ubiquitously expressing mCRY1 with a mutation by which cysteine414 (the zinc-binding site of mCRY1 [7, 8]) was replaced by alanine. In addition to unusual circadian rhythms in locomotor activities [4, 9], Tg mice showed early-onset diabetes mellitus similar to maturity-onset diabetes of the young (MODY) characterized by β -cell dysfunction [36].…”
Section: Introductionmentioning
confidence: 99%
“…We previously generated transgenic mice (previously labeled as CRY1-AP Tg mice [46] or afterward C414A CRY1 Tg mice [3]: hereinafter designated as Tg mice) ubiquitously expressing mCRY1 with a mutation by which cysteine414 (the zinc-binding site of mCRY1 [7, 8]) was replaced by alanine. In addition to unusual circadian rhythms in locomotor activities [4, 9], Tg mice showed early-onset diabetes mellitus similar to maturity-onset diabetes of the young (MODY) characterized by β -cell dysfunction [36]. An earlier report described that lowered proliferation of β -cells is accountable for age-dependent loss of β -cells in Tg mice [3, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation